2023
DOI: 10.1021/acsnano.2c11777
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Janus Nanoplatform for Efficiently Synergistic Theranostics of Rheumatoid Arthritis

Abstract: Progress has been made in the application of nanomedicine in rheumatoid arthritis (RA) treatment. However, the whole process of monitoring and treatment of RA remains a formidable challenge due to the complexity of the chronic autoimmune disease. In this study, we develop a Janus nanoplatform (denoted as Janus-CPS) composed of CeO2–Pt nanozyme subunit on one side and periodic mesoporous organosilica (PMO) subunit on another side for simultaneous early diagnosis and synergistic therapy of RA. The Janus nanostru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…[ 172 ] Liu and colleagues showed that a similar approach can be used for simultaneous early diagnosis and synergistic rheumatoid arthritis therapy. [ 173 ]…”
Section: Combination Of Several Types Of Anisotropymentioning
confidence: 99%
“…[ 172 ] Liu and colleagues showed that a similar approach can be used for simultaneous early diagnosis and synergistic rheumatoid arthritis therapy. [ 173 ]…”
Section: Combination Of Several Types Of Anisotropymentioning
confidence: 99%
“…Reproduced with permission. [ 126 ] Copyright 2023, American Chemical Society. c) Distribution of ICG, A‐nanoceria‐ICG, and PEG‐nanoceria‐ICG over time by multispectral optoacoustic tomography (grey: ultrasound, red: oxygenated hemoglobin, green: ICG).…”
Section: Nanozymes Applications In Bone Diseasesmentioning
confidence: 99%
“…developed a Janus nanoplatform (Janus‐CPS) consisting of CeO 2 –Pt nanozymes subunits on one side and periodic mesoporous organosilica subunits on the other side for simultaneous early diagnosis and synergistic treatment of RA (Figure 15b). [ 126 ] By combining the NIR dye indocyanine green (ICG) into the nanoplatform, Janus‐CPS‐MI have NIR II fluorescence imaging capability, allowing the detection of RA at an early stage. In addition, nanoparticles developed by Kalashnikova achieved inflammatory targeting, therapeutic, and imaging functions by coupling cerium dioxide nanoparticles to albumin and ICG.…”
Section: Conclusion and Future Prospectivementioning
confidence: 99%
“…Rheumatoid arthritis (RA) is a serious threat to human health as it can cause inflammation, swelling, and pain in the joints, severely damaging the joints over time and eventually leading to progressive disability and systemic complication. Currently, conventional imaging techniques for RA diagnosis mainly rely on X-ray, CT, MRI, and ultrasonography. However, these existing methods are limited by potential radiation hazards, low sensitivity and specificity, poor spatial and temporal resolution, which provide insufficient information to understand the biological processes underlying the pathology of RA disease, thus fail to diagnose RA disease early . Therefore, there is still an urgent need to develop highly sensitive, selective, and nonradioactive bioimaging methods for real-time diagnosis of early RA to assess pathological changes in RA.…”
Section: Introductionmentioning
confidence: 99%